Dynamics of rotation of super-Earths - Callegari Jr., Nelson [UNESP]; Rodríguez, Ádrian (Springer Nature, 2013)
We numerically investigate the dynamics of rotation of several close-in terrestrial exoplanet candidates. In our model, the rotation of the planet is disturbed by the torque of the central star due to the asymmetric equilibrium figure of the planet. We model the shape of the planet by a Jeans spheroid. We use surfaces of section and spectral analysis to explore numerically the rotation phase space of the systems adopting different sets of parameters and initial conditions close to the main spin-orbit resonant states. One of the parameters, the orbital eccentricity, is critically discussed here within the domain of validity of orbital circularization timescales given by tidal models. We show that, depending on some parameters of the system like the radius and mass of the planet, eccentricity etc., the rotation can be strongly perturbed and a chaotic layer around the synchronous state may occupy a significant region of the phase space. 55 Cnc e is an example. © 2013 Springer Science+Business Media Dordrecht.
Keywords: 55 Cnc planets; CoRoT-7 planets; GJ 876d; KOI-55 planets; Spin-orbit resonance; Terrestrial exoplanets